Telaah Qur’ani terhadap Kebutuhan dan Keinginan dalam Ekonomi Islam - S, MUZAKKIR. (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2024)
The outbreak of the culture of consumerism and hedonism is a phenomenon that is currently quite troubling. This research reveals the Qur'anic view of the concept of needs and desires, which is often blurred in its meaning and application. The complexity of the Qur'an is certainly able to answer that, but different interpretations and understanding of the content of the Qur'an are the reasons for differences in attitudes and applications in one concept. This research is a qualitative study with a library research approach using the thematic interpretation method (maudhū'ī). In the reality contained in the Qur'an, needs are primary and essential and desires are secondary and tertiary with the purpose and risk of both being clear, namely the need for prosperity and desire for mere satisfaction. Legally, needs are permissible and recommended by the Shari'ah while desires are permissible with terms and conditions that do not violate the rules of Islamic teachings.